3D‐printed Franz type diffusion cells. (27th December 2018) - Sil, B. C.; Alvarez, M. P.; Zhang, Y.; Kung, C‐P.; Hossain, M.; Iliopoulos, F.; Luo, L.; Crowther, J. M.; Moore, D. J.; Hadgraft, J.; Lane, M. E.; Hilton, S. T.
Abstract: Objective: Franz cells are routinely used to measure in vitro skin permeation of actives and must be inert to the permeant under study. The aim of the present work was to develop and manufacture transparent Franz‐type diffusion cells using 3D printing. Printouts were then tested using a range of model active compounds. The study also aims to identify the critical 3D‐printing parameters necessary for the process, including object design, choice of printing resin, printout curing and post‐curing settings and introduction of model coatings. Methods: Transparent Franz cells were constructed using an online computer aided design program and reproduced with different stereolithography 3D printers. The two acrylate‐based resins used for the fabrication process were a commercially available product and a polymer synthesised in‐house. Comparative studies between glass and 3D‐printed Franz cells were conducted with selected model actives: terbinafine hydrochloride (TBF), niacinamide (NIA), diclofenac free acid (DFA) and n‐methyl paraben (MPB). In preliminary studies, MPB showed the lowest recovery when exposed to the receptor compartment of 3D printed cells. Consequently, in vitro permeation studies were carried out using only MPB with polydimethylsiloxane (PDMS) membrane. Results: A decrease in the amounts of selected compounds was observed for transparent 3D‐printed Franz cells compared to glass cells. MPB showed the lowest recovery (53.8 ± 13.1%) when compared with NIA (74.9 ± 4.0%), TBF (81.5 ± 12.0%) and DFA (90.2 ± 12.9%) after 72 h. Permeation studies conducted using 3D‐printed transparent cells with PDMS membrane also showed a decrease in MPB recovery of 51.4 ± 3.7% for the commercial resin and 94.4 ± 3.5% for the polymer synthesised in‐house, when compared to glass cells. Although hydrophobic coatings were subsequently applied to the 3D‐printed cells, the same reduction in MPB concentration was observed in the receptor solution. Conclusion: Transparent Franz cells were successfully prepared using 3D printing and were observed to be robust and leak‐proof. There are few resins currently available for preparation of transparent materials and incompatibilities between the actives investigated and the 3D‐printed cells were evident. Hydrophobic coatings applied as barriers to the printed materials did not prevent these interactions. Abstract : Franz cells are routinely used to measure in vitro skin permeation of active ingredients and must be inert to the permeant under study. The aim of the present work was to develop and manufacture transparent Franz‐type diffusion cells, using 3D printing and test these using a range of model active compounds.